2021
DOI: 10.17126/joralres.2021.031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the mental foramen location in a sample of Saudi Al Hasa, population using cone-beam computed tomography technology: A retrospective study.

Abstract: Background: It is essential that the dentist understand the positional variations of the mental foramen to perform different types of dental procedures. This study was conducted to identify the position of the mental foramen among the Saudi population of Al Hasa. Material and Methods: According to the selection criteria of 200 CBCT images, 101 images were selected. The selected images were categorized into five groups with respect to patient age. Each image was evaluated from both sides of the mandible and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Aldosimani et al showed that the MF was located close to the mandibular second premolar in a statistically significant number (more than 68.1%) of participants from the central area of the Kingdom [ 17 ]. Furthermore, separate studies conducted by Mahabob et al and Srivastava revealed that the location of MF below the second premolars was observed in the eastern and northern regions [ 10 , 11 ], respectively. These studies utilized CBCT images to disclose the MF, while in this study, OPG images were used to identify the position of the MF among the orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldosimani et al showed that the MF was located close to the mandibular second premolar in a statistically significant number (more than 68.1%) of participants from the central area of the Kingdom [ 17 ]. Furthermore, separate studies conducted by Mahabob et al and Srivastava revealed that the location of MF below the second premolars was observed in the eastern and northern regions [ 10 , 11 ], respectively. These studies utilized CBCT images to disclose the MF, while in this study, OPG images were used to identify the position of the MF among the orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%
“…After conducting a comprehensive review of the literature, it was found that only a few studies have shown the prevalence of MF in a population from Saudi Arabia. These investigations were conducted in various parts of the nation, including the central, northern, and eastern regions, and used CBCT as the imaging technique [ 8 , 10 , 11 ]. The aforementioned research examined many anatomical characteristics of MF, including the placement of MF, the trajectory of the MN, and proximity to neighboring cortical plates.…”
Section: Introductionmentioning
confidence: 99%